Photoirradiation‐ and Extracellular‐Matrix‐Encouraged Photon‐Transition Switching Regulates Spatiotemporal Sequential Photoimmunotherapy - Hai Wang; Feixiang Hu; Wuyang Wei; Wencheng Wu; Qiaoling Yang; Wen Qin; Chao Fang; Xiulin Dong; Yang Zhou; Kun Zhang (Small Structures)
As two main phototherapy means, photodynamic therapy (PDT) and photothermal therapy (PTT) have different photon‐transition avenues decided by the aggregation state of photosensitizers (PSs), and thus PDT or PTT efficiency can be regulated by regulating PSs aggregation. A co‐assembly formulation consisting of IR780 iodide PSs and pentafluorophenyl trifluoroacetate is constructed through intermolecular interactions, followed by coating with hyaluronic acid. Initially, the uniform distribution of IR780 PSs favors more reactive oxygen species birth to implement PDT when entering cells since its photon‐transition avenue through the sequential process intersystem crossing transfer–collision energy transfer is predominant. After hyaluronidase and laser irradiation‐induced structural collapse of co‐assembly, free IR780 aggregates due to hydrophobic interactions even though they are excreted out of cells, and then, these IR780 aggregates produce heat through the nonradiative relaxation process to execute PTT. Such a spatiotemporal sequential PDT–PTT phototherapy encourages antitumor immune responses and mitigates immunosuppression, thus accomplishing the spatiotemporal sequential photoimmunotherapy against breast cancer progression. Through such tumor microenvironment‐adaptable and laser‐duration‐decided aggregation state alteration, photon‐transition switching is regulated and more insights are provided into single PSs‐mediated sequential PDT–PTT and photoimmunotherapy.